Usage of Alfalfa hay stalks treated with different levels of urea and mo-lasses in fattening rations of Al-Naimi lambs - Mohamed, Ayoob Ahmed; Lazim , Jameel Sarhan; Azzawi, Muthanna Sabah (Journal of Kerbala for Agricultural Sciences, 2023)
The experiment was conducted in the animal field belonging to the Department of Animal Production Techniques at the Technical College / Al-Mussaib for a period from 29/10/2021 to 21/1/2022 to study usage of Alfalfa hay stalks treated with urea and molasses in the productive performance of Al-Naimi lambs, which had initial weight of 20 ± 1 kg and at the age of 4-5 months, at a rate of 84 days, preceded by a preparatory phase for two weeks, and the lambs were randomly divided into five equal groups (5 lambs for each), and the individual feeding method was followed, as concentrated feed was provided at a rate of 2.5% of the live weight for each animal and fed on the five experimental rations,that the roughage feed Alfalfa hay stalks was given free, the first group (T1) was considered as a control without addition, (T2) and (T3) groups were treated with 4% urea with the addition of either 6% molasses or 12% molasses respectively, (T4) and (T5) groups were treated with 6% urea with the addition of either 6% molasses or 12% molasses respectively, and the results were as follows: Lambs of the fourth group (T4: 6% urea with 6% molasses) responded to fattening with a significant increase (P<0.05) and by 67.95% in weight gain and by 15.7% in consumption of concentrated and roughage feed compared with the control group (T1) and the other groups, which may indicate the efficiency of digestion and benefit of the diet treatment with 6% urea and 6% molasses added to free-fed Alfalfa hay stalks of Al-Naimi fattening lambs.